Physiology and yield of piel de sapo melon (Cucumis melo L.) under water deficit in semi-arid region, Brazil (Bioscience Journal, 2020)
Melon (Cucumis melo L.) is a crop of great socioeconomic importance in regions with semiarid climate, as found in Northeast Brazil. In this region water deficit is a usual condition as well as the main reduction factor of plant productivity. Due to this phenomenon, irrigation techniques are used to make available the amount of water needed for plant production. Therefore, this research evaluated the physiology and fruit production changes of ‘Juazeiro’ Piel de sapo melon plants under different water replacement rates. ‘Juazeiro’ melon was grown under four reference evapotranspiration replacement rates (40, 60, 80 and 100% of ETo) distributed randomly in blocks with 5 replicates. The plants were cultivated in the field, in an experimental area located in the Brazilian Northeast region, under hot and dry semiarid climatic conditions, and during the growing cycle the ‘Juazeiro’ hybrid melon plants were evaluated for leaf area, biomass accumulation, gas exchange, photochemical efficiency of photosystem PSII and production of fruits per plant. Application of water replacement rates of 100% ETo leads to highest growth, net photosynthesis, and fruit yield of 'Juazeiro' melon. Water replacement at 80% ETo can be used for ‘Juazeiro” melon under semiarid climatic conditions, but with small losses in fruit yield. Water replacement below 80% ETo leads to drastic reductions in growth, gas exchanges, quantum efficiency of photosystem II and fruit yield, which impairs melon production in semi-arid climate environments.